Psychological Dynamics among Adolescents with Self-Harm Behavior Based on Rational Emotive Behavior Therapy - Hidayatullah, Hengki Tri; Setiyowati, Arbin Janu; Simon, Irene Maya; Indriyati, Riyani; Mattingly, Maria Teresa (Jurnal Kajian Bimbingan dan Konseling, 2024)
The objective of this study was to ascertain the psychological underpinnings of self-harm behaviors among adolescents, with a particular emphasis on the tenets of rational emotive behavior therapy (REBT). Additionally, this study aimed to elucidate the various forms of self-harm behaviors and the underlying factors that contribute to these behaviors in adolescents. This research employed a qualitative approach with a phenomenological research design. The research subjects were students at State Senior High School 1 Batu, Indonesia, selected based on certain criteria in accordance with the research needs (purposive sampling). The results demonstrate three key aspects of the psychological dynamics of adolescents with self-harm behavior, namely cognitive, affective, and conative. These were mapped into the ABC model, which comprises three elements, namely activating events, irrational beliefs, and impacts. Forms of self-harm in adolescents include physical (slashing the hand) and non-physical (ignoring health, smoking, taking drugs, and staying up late). The background of adolescents committing self-harm behavior is influenced by both internal factors (dissatisfaction and loneliness) and external factors (family problems and modeling).